Pulse contour analysis calibrated by Trans-pulmonar thermodilution (Picco Plus ® ) for the perioperative management of a caesarean section in a patient with severe cardiomyopathy - Brogly,Nicolas (2016)
ABSTRACT BACKGROUND: The delivery of cardiac patients is a challenge for the anaesthesiologist, to whom the welfare of both the mother and the foetus is a main issue. In case of caesarean section, advanced monitoring allows to optimize haemodynamic condition and to improve morbidity and mortality. OBJECTIVE: To describe the use of pulse contour analysis calibrated by Trans-pulmonar thermodilution (Picco Plus® for the perioperative management of a caesarean section in a patient with severe cardiomyopathy. CASE REPORT: We describe the case of a 28-year-old woman with a congenital heart disease who was submitted to a caesarean section under general anaesthesia for maternal pathology and foetal breech presentation. Intra- and post-operative management was optimized by advanced haemodynamic monitorization obtained by pulse contour wave analysis and thermodilution calibration (Picco Plus® monitor). The information about preload, myocardial contractility and postcharge was useful in guiding the fluid therapy and the use of vasoactive drugs. CONCLUSION: This case report illustrates the importance of advanced haemodynamic monitoring with an acceptably invasive device in obstetric patients with high cardiac risk. The increasing experience in advanced haemodynamic management will probably permit to decrease morbidity and mortality of obstetric patients in the future.